Digital Literacy of Tourism Awareness Groups in Digital Promotion Activities of Cibuntu Tourism Village, Kuningan Regency - Yoka Pradana; Aiza Nabila Arifputri; Rizca Haqqu (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
Cubuntu tourist village in Kuningan Regency is an outstanding tourist village actively participating in digital promotion. The success of digital tourism promotion is closely related to the digital literacy skills of tourist village managers. This study aims to analyze the digital literacy of the Cibuntu village tourism awareness group (Pokdarwis) in digital promotion activities. The research method used is qualitative with a case study design. Data were obtained from interviews with four members of the Pokdarwis of Cibuntu village in the field of promotional media and observation of the Cibuntu village promotional media. The results showed that the digital literacy of Pokdarwis Cibuntu village has various aspects of digital skills, including information literacy, communication, and collaboration skills, the ability to develop digital content creation, and the ability to secure digital data. Meanwhile, the ability to solve problems using digital technology has not been able to be done, and the ability to create digital content has been done, but not entirely. The contribution of this research shows that the digital literacy skills possessed by the Pokdarwis of Cibuntu village are learned independently through content on social media. The findings are a consideration for tourism village managers in other regions to encourage Pokdarwis members to learn independently about digital promotion activities amid the wealth of information on social media.